Sensitive and selective non-enzymatic rGO/ZIF-8 hybrid composite-based electrochemical sensor for uric acid detection: optimisation by response surface methodology - Suratman, Anis Afiqah; Che Zakaria, Aida Zafierah; Abdul Aziz, Siti Fatimah Nur; Alang Ahmad, Shahrul Ainliah (Elsevier, 2024)
The development of a cost-effective, straightforward, mobile and highly sensitive sensing platform for the rapid uric acid detection is desirable to advancing early diagnostic methods. Zeolitic imidazolate framework (ZIF) was used in the construction of electrochemical sensing platform because their properties can be adjusted by tuning their topology and porosity, allowing them to be advantageous for achieving sensitive, rapid response, selective, and low-cost operation in sensing applications. However, most ZIFs are insulators with lower conductivities. In this study, we present a hybrid of zeolitic imidazolate framework-8 (ZIF-8) on electrochemically reduced graphene oxide (rGO) for the monitoring of uric acid in physiological samples. The hybrid layer, coated onto an electrode was parametrically characterized by powder X-ray diffraction (PXRD), Fourier transform infrared (FTIR), cyclic voltammetry (CV) and further optimised through a statistical approach, response surface methodology (RSM). A central composite design was employed to examine the influence of three independent variables, i.e., volume, pH and deposition time to provide an insight into the sensing performance of the ZIF-8/rGO electrode.This ZIF-8/rGO hybrid exhibited a timely response to uric acid within a linear concentration range of 20 to 400 μM, achieving a detection limit of 0.97 μM and demonstrating excellent selectivity. Moreover, the comparison of percentage recovery for the developed sensor in urine and blood samples was remarkably similar to that of the commercial uric acid meter. This indicates reliable and highly accurate performance, suggesting the developed sensor functions effectively as a commercially available uric acid.